2019
DOI: 10.1002/qre.2546
|View full text |Cite
|
Sign up to set email alerts
|

Control charts for simultaneously monitoring of process mean and coefficient of variation with and without auxiliary information

Abstract: A control chart is very useful to control assignable causes which detect the shifted process parameters (eg, mean and dispersion). Simultaneous monitoring of the process parameters is a well‐known approach utilized for the bilateral processes. In the current study, we proposed the blended control chart that monitors the process mean and process coefficient of variation simultaneously. Further, the sensitivity of control chart is enhanced by incorporating an auxiliary variable. We have utilized the concept of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Subsequently, numerous new studies were done on γ‐type charts. Among them are the Exponentially Weighted Moving Average (EWMA) charts, 1,10,13–17 run rules chart, 18 run sum chart, 19 side sensitive group runs chart, 20 charts with variable charting parameters, 11,21–24 charts with measurement errors, 25,26 joint monitoring of μ and γ, 27 and the Phase I performance of γ‐type charts 28 …”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, numerous new studies were done on γ‐type charts. Among them are the Exponentially Weighted Moving Average (EWMA) charts, 1,10,13–17 run rules chart, 18 run sum chart, 19 side sensitive group runs chart, 20 charts with variable charting parameters, 11,21–24 charts with measurement errors, 25,26 joint monitoring of μ and γ, 27 and the Phase I performance of γ‐type charts 28 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Haq et al [22] suggested AIB adaptive Crosier CUSUM (ACC AIB ) under fixed and variable sampling intervals and AIB adaptive EWMA (AE AIB ) control charts for the monitoring of PLOS ONE process mean. For more details about adaptive EWMA, hybrid EWMA, and AIB memory control charts, see [23][24][25][26][27] and reference therein.…”
Section: : Introductionmentioning
confidence: 99%
“…Recently, Muhammad et al 14 proposed a variable sample size EWMA CV chart, and Yeong et al 15 proposed the variable parameter CV monitoring chart. Noor-ul-Amin et al 16 suggested a simultaneous process monitoring process mean and CV in the presence of auxiliary and non-auxiliary data, and the Riaz and Noor-ul-Amin 17 proposed the simultaneous scheme for the process mean and CV under ranked set sampling.…”
Section: Introductionmentioning
confidence: 99%